Analysis of the sensitivity of the construction cost of a one-storey residential building to design wind speeds - Adizas, Marc Neil V.; Aquino, Diocel Harold M. (Quezon City College of Engineering, University of the Philippines Diliman, 2015)
Over the past decade, Philippines has been experiencing super typhoons that have never recorded before. These natural disasters have caused extreme damage to properties and significant threat to human life. That is why there have been proposals to change the current basic design wind speeds and wind zone map of the country. In order to strengthen the knowledge within the proposals, there is a need to analyze the sensitivity of the building construction cost to changes in the design wind speed. A model of a typical one-storey residential building shall be analyzed and modified through varying design wind speeds from 100 kilometers per hour (kph) to 325 kph with increments of 25 kph. Wind-sensitive components shall be identified with the corresponding costs of materials used. The process is repeated for all design wind speeds. Sensitivity analysis shall be carried out from the total building cost and design wind speed. Implication of the sensitivity analysis will be used to analyze the affected provinces with the change in design wind speeds based on the proposed 2014 wind zone map. Parameters obtained can be used as reference for future use.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Buildings -- Aerodynamics; Winds -- Speed -- Philippines -- Maps; Construction industry -- Costs